The prehospital management of ambulance-attended adults who fell: A scoping review. (March 2023) - Watkins, Paige Marie; Masters, Stacey; Hill, Anne-Marie; Tohira, Hideo; Brink, Deon; Finn, Judith; Buzzacott, Peter
Abstract: Background: The ageing population is requiring more ambulance attendances for falls. This scoping review aimed to map and synthesise the evidence for the prehospital management of Emergency Medical Services (EMS) attended adult patients who fall. Methods: The Joanna Briggs Institute methods for scoping reviews were used. Six databases were searched (Medline, Scopus, CINAHL, Cochrane, EMBASE, ProQuest), 1st August 2021. Included sources reported: ambulance attended ( context ), adults who fell ( population ), injuries, interventions or disposition data ( concept ). Data were narratively synthesised. Results: One-hundred and fifteen research sources met the inclusion criteria. Detailed information describing prehospital delivered EMS interventions, transport decisions and alternative care pathways was limited. Overall, adults< 65 years were less likely than older adults to be attended repeatedly and/or not transported. Being male, falling from height and sustaining severe injuries were associated with transport to major trauma centres. Older females, falling from standing/low height with minor injuries were less likely to be transported to major trauma centres. Conclusion: The relationship between patient characteristics, falls and resulting injuries were well described in the literature. Other evidence about EMS management in prehospital settings was limited. Further research regarding prehospital interventions, transport decisions and alternative care pathways in the prehospital setting is recommended.